COST MONITORING AS A TOOL IN THE BUSINESS LOGISTICS SYSTEM - PANCHENKO, Volodymyr; PANCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Aspects of enterprise cost management in the business logistics system are analyzed. It was found that the issue of quality cost management is much broader than the maintenance of financial and economic activity, because it is especially relevant in the business logistics system, determining its stability and a number of important issues of economic and, in particular, industrial safety. The purpose of the article is to improve the cost monitoring system as an important tool in the structure of business logistics. Methods of synthesis and system analysis were applied (to substantiate the essential characteristics of costs in the enterprise's logistics system); system analysis and theoretical generalization (to improve the classification of an enterprise's costs in its logistics system). It has been investigated that the creation of effective analytical support for the management of current costs in the logistics system of the enterprise is related to: the production of competitive products, the availability of high-quality and real information on the cost of certain types of products, performed works (services) and their positions on the market. A general model of the economic analysis of the company's current costs has been developed. The company's current expenses have been grouped according to classification criteria. A classification of the current costs of the enterprise's interaction with the subjects of the external market environment has been developed. The company's current costs are classified by cost calculation items in the business logistics system. It was established that in the conditions of a complex external business environment, there is a problem in determining current costs, their distribution by objects and ensuring their minimization, their management and recognition of expediency, achieving the necessary profitability. It was found that the main task is not to minimize them, but to reach such a level that they are recognized by consumers and bring profit to producers. It has been studied that all this is achieved due to the formation and implementation of a proper strategy for managing the current costs of the enterprise. It is summarized that the decisive factors in the system of complex economic analysis and in the analytical provision of the grouping of costs according to the scheme "activity - costs - financial result" are their grouping by economic elements (material, labor costs, social measures, depreciation and other operating costs) and articles calculations It is shown that a promising direction of further research in this area is the improvement of the method of analyzing the cost intensity in the industrial safety system of enterprises.
Keywords: enterprise management; logistics; business; enterprise costs; monitoring